Carboplatin versus two doses of cisplatin in combination with gemcitabine in the treatment of advanced non-small-cell lung cancer: Results from a British Thoracic Oncology Group randomised phase III trial. (September 2017) - Ferry, David; Billingham, Lucinda; Jarrett, Hugh; Dunlop, David; Woll, Penella J.; Nicolson, Marianne; Shah, Riyaz; Thompson, Joyce; Spicer, James; Muthukumar, D.; Skailes, Geraldine; Leonard, Pauline; et al.
Abstract: Background: Platinum-based combination chemotherapy is standard treatment for the majority of patients with advanced non-small-cell lung cancer (NSCLC). The trial investigates the importance of the choice of platinum agent and dose of cisplatin in relation to patient outcomes. Methods: The three-arm randomised phase III trial assigned patients with chemo-naïve stage IIIB/IV NSCLC in a 1:1:1 ratio to receive gemcitabine 1250 mg/m 2 on days 1 and 8 of a 3-week cycle with cisplatin 80 mg/m 2 (GC80) or cisplatin 50 mg/m 2 (GC50) or carboplatin AUC6 (GCb6) for a maximum of four cycles. Primary outcome measure was survival time, aiming to test for a difference between treatment arms and also assess non-inferiority with pre-defined margin selected as hazard ratio (HR) of 1.2. Secondary outcome measures included response rate, adverse events and quality of life (QoL). Findings: The trial recruited 1363 patients. Survival time differed significantly across the three treatment arms (p = 0.046) with GC50 worst with median 8.2 months compared to 9.5 for GC80 and 10.0 for GCb6. HRs (adjusted) for GC50 compared to GC80 was 1.13 (95% confidence interval [CI] 0.99–1.29) and for GC50 compared to GCb6 was 1.23 (95% CI: 1.08–1.41). GCb6 was significantly non-inferior to GC80 (HR = 0.93, upper limit of one-sided 95% CI 1.04). Adjusting for QoL did not change the findings. Best objective response rates were 29% (GC80), 20% (GC50) and 27% (GCb6), p < 0.007. There were more dose reductions and treatment delays in the GCb6 arm and more adverse events (60% with at least one grade 3–4 compared to 43% GC80 and 30% GC50). Interpretation: In combination with gemcitabine, carboplatin at AUC6 is not inferior to cisplatin at 80 mg/m 2 in terms of survival. Carboplatin was associated with more adverse events and not with better quality of life. Cisplatin at the lower dose of 50 mg/m 2 has worse survival which is not compensated by better quality of life. ClinicalTrials.gov identifier: NCT00112710 . EudraCT Number: 2004-003868-30. Cancer Research UK trial identifier: CRUK/04/009. Highlights: Large randomised phase III trial in advanced non-small cell lung cancer is reported. Platinum-based chemotherapy remains standard first-line treatment for majority. Trial provides definitive evidence-base for choice of platinum in this setting. Cisplatin 50 mg/m 2 gives inferior survival, not compensated by better quality of life. Carboplatin AUC6 is not inferior to cisplatin 80 mg/m 2 in terms of survival time and is not associated with better quality of life.